NEW PROPERTIES OF NATURAL RADIOACTIVITY - Bakhodir Abdusamatovich Mirsalikhov; Saytdjanov Shovkat Nigmatjanovich; Xusniddinov Faxriddin Shamsiddinovich (European Science Publishing, 2024)
This article contains a brief description of the new properties of radioactivity in nuclear physics. In accordance with it, the interpretation of new types of beta emirate, the process of formation of photonuclei and photonuclei are explained by reaction mechanisms.
Keywords: nuclear physics, radioactivity, star, nucleon, atom, gamma, photonucleus, reaction, antineutrino, electron-pozitron.